Bridging Diverging Perspectives and Repairing Damaged Relationships in the Aftermath of Workplace Transgressions. Issue 3 (July 2014) - Okimoto, Tyler G.; Wenzel, Michael
ABSTRACT: Workplace transgressions elicit a variety of opinions about their meaning and what is required to address them. This diversity in views makes it difficult for managers to identify a mutually satisfactory response and to enable repair of the relationships between the affected parties. We develop a conceptual model for understanding how to bridge these diverging perspectives and foster relationship repair. Specifically, we argue that effective relationship repair is dependent on the parties' reciprocal concern for others' viewpoints and collective engagement in the justice repair process. This approach enhances our understanding of the interdependency between justice and reconciliation/reintegration, while also providing theoretical insight into the processes underlying restorative conferencing, innovations that promise to help managers heal damaged organizational bonds.